2009
DOI: 10.5551/jat.760
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lifestyle-Related Diseases on Carotid Arterial Wall Elasticity as Evaluated by an Ultrasonic Phased-Tracking Method in Japanese Subjects

Abstract: Aim:We investigated the relationship between coronary risk factors and the intima-media thickness (IMT) and wall elasticity of carotid arteries. A new real-time ultrasonic measurement system that allows measurement of the elasticity of the carotid arterial intima-media complex was applied to 350 subjects, who were also checked for the presence/absence of hypertension, dyslipidemia, diabetes mellitus and regular smoking. Simultaneous measurement of the elastic modulus and IMT was conducted at four sites in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…IMT is used as a criterion for atherosclerosis [8,9]. Increased IMT detected by ultrasound reflects morphological changes including thickening and calcification of carotid artery [17]. Increased IMT is considered as an indicator of increased risk for myocardial infarction and stroke [9,18].…”
Section: Discussionmentioning
confidence: 99%
“…IMT is used as a criterion for atherosclerosis [8,9]. Increased IMT detected by ultrasound reflects morphological changes including thickening and calcification of carotid artery [17]. Increased IMT is considered as an indicator of increased risk for myocardial infarction and stroke [9,18].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our method enables the measurement of elasticity distribution in the intima-medial region by ultrasound and the evaluation of local (lesion) elastic properties by measuring mural thickness change. In a previous study, age, blood pressure and pulse rate were shown to be independent determinants of the average values E of elasticity distribution 15) . In the present study, an elasticity library with transcutaneous ultrasound was obtained by observing various tissues of the carotid arterial wall (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…An imaging study of the bilateral common carotid arteries was performed using a newly developed high-resolution ultrasonic measurement system (Panasonic, prototype) with a center frequency of 7.5 MHz. One well-trained sonographer who regularly participates in quality control measurement sessions performed all ultrasound scans 13,15) . The sonographer has been trained to obtain an elastic modulus measurement deviation of only 6% in the same subject (inter-and intra-variations were less than 10% at our institution).…”
Section: Carotid Imt and Elasticity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for CIMT, the presence of atherosclerotic plaque in the carotid artery has consistently been associated with cardiovascular risk factors and with prevalent and incident vascular events [4][5][6][7][8][9][10][11][12][13][14][15] . Moreover, measurement of changes in plaque volume may be of value in assessing changes in atherosclerotic burden over time, as some studies have found a stronger association with vascular events for plaques than for CIMT 4,5,7,11,13) .…”
Section: Introductionmentioning
confidence: 99%